Between reason and the will to power – Thomas Mann’s world view during the First World War - Jacek Kępa (Przestrzenie Teorii)
The work entitled “Reflections of an Unpolitical Man”, written during World War I, includes an essay against the Western states. Thomas Mann compares democratic countries and the societies created after the French Revolution with the German concept of society and a country based on conservative values. Equality is set against hierarchy, the individual against the community, and a secular perspective against a religious one. Defiance of the West is based on Protestantism. The references to Nietzsche and Schopenhauer, in agreement with Darwin's theory of evolution, are advanced by the West as an argument for the conflict between rationalism and irrationalism. At the end of Thomas Mann’s work, this conflict is solved by the “principle of irony”, which gives the author the opportunity to reconcile himself with the concept of democracy. This also dominated his future work.